Quantitative Reasoning is a Key Factor for High School Students - Carazas, Rafael Romero-; Castañeda, Elena Esther Yaya; Narvaste, Bertha Silva-; Quezada, Pedro Ricardo Quiroz-; Meniz, Patricia Demetria Osorio-; Hernández, Bryam Alejandro Colán- (International Journal of Membrane Science and Technology, 2023)
The present study aimed to analyze the process of development of quantitative reasoning in high school students. A literature review study was applied through a content analysis, performing a search in the databases a) Scopus, b) SciELO, c) Dialnet, d) Latindex and e) Google Academic, using as keywords: a) quantitative reasoning b) secondary education students, c) quantitative literacy, d) pedagogical practice, e) teaching/learning and selecting through a sampling based on the following criteria: a) original scientific articles or review, b) publications in Spanish or English, c) time period between the first and the second year of the study. 2015-2023, d) undergraduate these included in institutional repositories and e) citable documents, allowing to discriminate a total of 40 articles to be reviewed. The analysis of the texts made it possible to identify three categories of analysis a) Quantitative reasoning opening paths for the development of systematic thinking, b) Language and literature essential elements for the development of quantitative reasoning and c) The role of Information and Communication Technologies (TIC) in the development of quantitative reasoning, concluding that quantitative reasoning helps students to learn to properly use and evaluate quantitative information and build arguments.